EXPLORATION OF NON-MUSLIM COMMUNITY'S DECISION TO BECOME THIRD PARTY FUND CUSTOMERS AT BANK SUMUT CAPEM SYARIAH PERDAGANGAN: ANALYSIS OF SERVICE QUALITY AND PERCEPTION OF FAIRNESS OF PROFIT SHARING - Ponco Setio Wijaksono; Muhammad Irwan Padli Nasution; Andri Soemitra (CV. Radja Publika, 2026)
This study aims to explore the decisions of non-Muslims to become Third Party Fund (DPK) customers at Bank Sumut Capem Syariah Perdagangan, focusing on service quality and perceptions of the fairness of the profit-sharing system. The study employed a descriptive qualitative approach with a case study method. The informants included branch managers, customer service representatives, fund marketers, and non-Muslim customers with sharia savings, current accounts, and time deposits. Data collection techniques included in-depth interviews, field observations, and documentation. Data analysis employed the Miles and Huberman model, which encompasses data reduction, data presentation, conclusion drawing, and verification. The results indicate that the decisions of non-Muslims to become DPK customers at Bank Sumut Capem Syariah Perdagangan are driven by rational and economic considerations. Inclusive, friendly, responsive, and non-discriminatory service quality builds initial customer trust in sharia banks. Furthermore, the profit-sharing system in Mudharabah products is perceived as fair, transparent, and profitable, as profits are aligned with fund management performance. For Wadi'ah products, customers consider competitive administration fees and bonuses attractive added value. Other factors influencing decisions include recommendations between traders and a heterogeneous social environment. Research findings indicate that the principles of fairness, transparency, and service quality are the primary reasons non-Muslims choose DPK products at Bank Sumut Capem Syariah Perdagangan.